Mathematical Modelling of Truck Platoon Formation Based on a Dynamic String Stability - Ajayi, Ore-Ofe; Umar, Abubakar; Ibrahim, Ibrahim; Olugbenga, Lawal Abdulwahab; Abiola , Ajikanle Abdulbasit (Vokasi Unesa Bulletin of Engineering, Technology and Applied Science, 2025)
In this research, the development of a fuzzy logic-based cooperative adaptive cruise control scheme for truck platooning string stability was developed. String stability, which is critical to the operation of truck platooning in the area of enhancing traffic flow and reducing fuel consumption can be affected by unknown uncertainties such as truck incapacitation, delay of platoons and inability to maintain a constant inter-vehicular gap. A commonly reported approach in addressing truck platooning string stability is the Cooperative Adaptive Cruise Control (CACC) scheme. The CACC scheme consists of Adaptive Cruise Control (ACC) and vehicle-to-vehicle (V2V) communication. However, the CACC lacks the requisite flexibility in dealing with unexpected disturbances that can result in the inability to maintain a constant speed and inter-vehicular gap.